EDUKASI INFLUENCER DI INSTAGRAM BERPENGARUH TERHADAP KESADARAN KHALAYAK (DI MASA PANDEMI COVID-19) - Fathonah Annisa (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2021)
Social media has created a new pattern of communication and social participation, which can be seen in the involvement of users in a social media forum or platform. Instagram social media has spawned powerful influencers in the dissemination of information as well as education via digital messaging. Influence is judged to have an impact on its followers by uploading photos, videos, and some other instagram facilities. At the beginning of the covid-19 BNPB (call upon a number of massive influence influence in Indonesia to downsize people. Research uses a quantitative approach with survey methods. The resulting data indicates that public awareness of health protocols at the time of the pandemic covid-19 was ata high level and was influenced by the soft influence in the instsalt has a postictal impact on public awareness of health protocols during the period of the pandemic covid-19.